Making cassava flour safe using the wetting method - J. Howard Bradbury; Julie Cliff; Jean P. Banea (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2015)
Many people, particularly in Africa, suffer various conditions from eating bitter cassava which contains poisonous cyanogens. As well as poisoning, which sometimes causes death, these conditions include konzo, an irreversible paralysis of the legs, which affects mainly children and young women, impaired neurocognition in children, tropical ataxic neuropathy in older people, and aggravation of iodine deficiency disorders (such as goitre and cretinism) in iodine deficient areas. The wetting method removes residual cyanogens, and is an additional method of processing cassava flour after its preparation by one of the traditional methods. The wetting method is simple and easy to use, the traditional thick porridge (fufu or ugali) made from the treated flour tastes very good, and the method is readily accepted by rural women in East and Central Africa. Regular use of the wetting method by rural women in 13 villages in the Democratic Republic of Congo has prevented konzo amongst more than 9,000 people. We recommend that the wetting method be used as an additional method to traditional methods to remove cyanogens from cassava flour in tropical Africa.